Characteristics of pneumonia deaths after an earthquake and tsunami: an ecological study of 5.7 million participants in 131 municipalities, Japan. Issue 2 (23rd February 2016) - Shibata, Yosuke; Ojima, Toshiyuki; Tomata, Yasutake; Okada, Eisaku; Nakamura, Mieko; Kawado, Miyuki; Hashimoto, Shuji
Abstract : Objective: On 11 March 2011, the Great East Japan Earthquake struck off Japan. Although some studies showed that the earthquake increased the risk of pneumonia death, no study reported whether and how much a tsunami increased the risk. We examined the risk for pneumonia death after the earthquake/tsunami. Design: This is an ecological study. Setting: Data on population and pneumonia deaths obtained from the Vital Statistics 2010 and 2012, National Census 2010 and Basic Resident Register 2010 and 2012 in Japan. Participants: About 5.7 million participants residing in Miyagi, Iwate and Fukushima Prefectures during 1 year after the disaster were targeted. All municipalities (n=131) were categorised into inland (n=93), that is, the earthquake-impacted area, and coastal types (n=38), that is, the earthquake-impacted and tsunami-impacted area. Outcome measures: The number of pneumonia deaths per week was totalled from 12 March 2010 to 9 March 2012. The number of observed pneumonia deaths (O) and the sum of the sex and age classes in the observed population multiplied by the sex and age classes of expected pneumonia mortality (E) were calculated. Expected pneumonia mortality was the pneumonia mortality during the year before. Standardised mortality ratios (SMRs) were calculated for pneumonia deaths (O/E), adjusting for sex and age using the indirect method. SMRs were then calculated by coastal and inland municipalities. Results: 6603 participants died of pneumonia during 1 year after the earthquake. SMRs increased significantly during the 1st–12th weeks. In the 2nd week, SMRs in coastal and inland municipalities were 2.49 (95% CI 2.02 to 7.64) and 1.48 (95% CI 1.24 to 2.61), respectively. SMRs of coastal municipalities were higher than those of inland municipalities. Conclusions: An earthquake increased the risk of pneumonia death and tsunamis additionally increased the risk.